Improving Effect of Ellagic Acid on Sleep Quality and Gastrointestinal Symptoms in Patient With Irritable Bowel Syndrome: Randomized Double-Blind Clinical Trial - Mirzaie, Zahra; Bastani, Ali; Hesami, Sepideh; Pouryousefi, Elahe; Kavianpour, Maria; Haghighian, Hossein Khadem (Turkish Journal of Gastroenterology, 2021)
Background: The quality of sleep in people with irritable bowel syndrome (IBS) is reduced by increased oxidative stress and clinical problems. Assessing the effects of ellagic acid (EA) on sleep quality and gastrointestinal symptoms in patients with IBS was the aim of this study. Methods: In this research that was conducted as a randomized, double-blind, placebo-controlled clinical trial, 44 patients with IBS were enlisted. Individuals approved by the project clinical counselor were divided into two intervention groups to receive 180 mg of EA per day (n = 22) and a placebo group (n = 22) for 2 months. Petersburg’s Sleep Quality (PSQI) questionnaire and IBS severity score system (IBSSS) were assessed at the beginning and end of the study. Statistical analysis was performed using SPSS software. Results: At the end of the study, changes in mean PSQI and scores related to sleep subgroups were significant between the two groups (P < .05). Also, the significant changes were not seen in sleep and sleep subgroups scores in the placebo group at the end of the study (P > .05). EA consumption reduced IBSSS score and IBS symptoms in the intervention group after 2 months (P < .05). Discussion: The results arisen from this study indicated that receiving EA had a beneficial effect on sleep quality and gastrointestinal symptoms in IBS patients. The antioxidant and anti-inflammatory properties of EA may be responsible for these beneficial effects